Tingkat Kedisiplinan Atlet Dalam Mengikuti Latihan Sepakbola Di Klub Noeklir FC - Wibiksana, Sopian; Hermawan, Irwan; Kurniawati, Ani (Universitas Hamzanwadi, 2025)
This study aims to determine the level of discipline of athletes in participating in soccer training and analyze the influence of the coach's role on this discipline. The approach used is quantitative with ex post facto method, which focuses on the relationship between variables that have occurred without manipulation. The population of this study were all Noeklir FC club athletes totaling 20 people, with total sampling technique. The instruments in this study were questionnaires, interviews, and observations. The results showed that the discipline of athletes in soccer training was quite good, with average scores for attendance, compliance with instructions, participation, and self-motivation reaching 80.937, 81.25, 80.937, and 79.062 respectively. Data analysis using descriptive statistics shows that good discipline can support the development of athletes individually and in teams, which ultimately contributes to the achievement of optimal performance in soccer competitions. This research indicates that the coach's role is very significant in shaping athlete discipline, which is a major factor in improving performance and achievement in the world of soccer.